Family entrepreneurship as an initiator of change in croatian tourism - Ivan Čapeta (UTMS Journal of Economics, 2023)
Purpose - The aim of this paper is to verify whether the "family entrepreneurship" model is an important development opportunity for Croatian tourism and whether family businesses, with their innovative approach to designing a tourist product, change the trends in the tourist market and whether they promote the differentiation of Croatian tourism on the global tourist market. Methodology - The paper examines the readiness of family businesses to present changing trends on the global tourism market through positive examples of innovative solutions of family businesses that contribute to the new direction of Croatian tourism, towards sustainable development. By comparing the performance of family businesses and tourism results at the national level, knowledge is gained about the contribution of family businesses in Croatian tourism. Findings - The results of the research indicated that family businesses contribute to the recognition of Croatia on the tourist market as a sustainable tourism destination with their innovative tourism products. Contribution - The conducted research can be the basis for further research on family businesses in the Republic of Croatia. Contributes to new knowledge about family entrepreneurship in tourism in the Republic of Croatia.
Keywords: M10; M21; L20; 330; family businesses; sustainable development; innovations in tourism; differentiation of the tourist product